A camada limite atmosférica marinha na confluência Brasil-Malvinas: uma comparação entre observações in-situ e ERA5 - Machado Machado, Raquel (2025)
The aim of the study was to compare the ERA5 reanalysis with in-situ data from the 41st Antarctic Operation, collected between October 19 and 21, 2022, at the Brazil-Malvinas Confluence. The results showed that the reanalysis underestimates the potential temperature and performed best on the 21st, when the boundary layer was stable. The reanalysis reasonably represents atmospheric conditions but has limitations in situations with a more turbulent boundary layer.